A COMPARATIVE STUDY OF AUTOMATION STRATEGIES AT VOLKSWAGEN IN GERMANY AND SOUTH AFRICA - Wessel, O.; Wessel, O. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The final car assembly lines at Volkswagen